Evaluasi Sistem Drainase untuk Antisipasi Limpasan Debit dengan Prinsip Zero Delta Q Studi Kasus: Perumahan The Savanna Batu - Asid, Nurul Jannah; Kucaravita, Sekar Ayu; Apriliani, Rizki Astri; Ridlwan, Yusuf (NAROTAMA JURNAL TEKNIK SIPIL, 2024)
Batu City as one of the tourist centers in East Java Province has resulted in the need for very fast property development. The Savanna complex is currently one of the most popular among consumers. One of the things that must be considered in housing construction is the wastewater and rainwater disposal system because it concerns the comfort of residents. Housing construction on land that was originally rice fields and catchments will cause problems related to additional water runoff. Based on this, a drainage system is needed that does not increase water runoff before and after construction. The Zero Delta Q policy is a "flood alert" concept by implementing restrictions on water runoff due to development where the difference between the water runoff discharge before construction and after construction must be 0 (zero). The current drainage channels use concrete pipes with a diameter of 0.6 m for primary channels and 0.4 m for secondary channels. After analyzing rainfall, topography and contour data as well as land use, planned discharge data for each channel was obtained. The existing channel dimensions can still meet the planned runoff discharge so there is no need to increase the channel dimensions. However, there was an increase in runoff discharge amounting to 2876,386 m3. Initially, before construction, the runoff discharge was 2331.3 m3. After construction, the runoff discharge was 2331.3 m3. 5207,731 m3. To minimize the difference in runoff discharge, 41 infiltration wells are planned with dimensions of 1.2 m wide and 3 m high..